The Black Madonna in the Italian American artistic imagination - Marino, Elisabetta (Acta neophilologica, 2017)
This essay sets out to explore the image of the black Madonna in Italian American artistic and literary expressions, providing thought-provoking examples of how this holy icon of universal motherhood has been persistently associated with the articulation of empowering strategies, with antagonism towards any kind of patriarchal restraints, with the healing of deeply ingrained divisions (of gender, class, ethnicity), and with the celebration of diversity in unity.
Keywords: American literature; ameriška književnost; art; Black Madonna; črna madona; Drugost; Italian Americans; italijanski Američani; Otherness; Patriarchy; patriarhalnost; umetnost